Effect of different build orientation on mechanical properties of fiberglass reinforced composite - Muhamad Khairul Izzat, Muhammad Atan (2009)
This thesis deals with effect of different build orientation on mechanical properties of fibreglass reinforced composite. The objective of this thesis is to investigate the mechanical properties of fibreglass reinforced composite with different build orientation, investigate the relation between fibreglass and polyester resin, and to understand on the mechanical behaviour of fibreglass reinforced composite. Fibreglass is refer to a group of products made from individual glass fibres combined into a variety of forms and act as reinforcing agent. The problem of bonding between fibreglass and the matrix resin affect the strength of the fibreglass reinforced composite and this need to be deals with the study on their mechanical properties by using mechanical experiment test. The test is carried out using tensile test, which all are focusing on investigating mechanical properties on the specimens. Fibreglass reinforced composite is made up by using hand lay-up technique, where different laminate of fibreglass made up by different build orientation of fibreglass which result different strength. The aim ofthe test is to study on this fibreglass reinforced composite strength and to observed on the mechanical behaviour of this material. It was found that by arranging the fibreglass properly, the stronger the fibreglass reinforced composite be.